Analisis Pengendalian Persediaan Barang Menggunakan Metode EOQ - Jonatan Persada Siregar; Rektor Sianturi; Debora Exaudi Sirait (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The aim of this research, based on the problem formulation above, is to find out that inventory management by using the Ecolnolmic Order Quantity (EOQ) met mode can minimize the total inventory costs UMKM Home Industry Rumah Tempe Asli HB Pematangsiantar. This thesis research uses a quantitative descriptive method. The method used in controlling tempe goods inventory is the EOQ method. The EOQ method is a inventory management technique carried out by the company by determining the most efficient inventory amount of goods and producing balanced processing costs and storage costs, so that The company can minimize inventory costs. From the results of research using the EOQ method, the total inventory carried out with the EOQ metdown is 80.179 pcs with a purchase frequency of 22 times. The amount of security stock required by UMKM Home Industry Rumah Tempe Asli HB Pematangsiantar is 8.200 pcs. Total inventory using the EOQ method is IDR Rp1.122.421. EOQ meting can reduce the costs of providing merchandise more or can be said to be efficient if applied to UMKM Home Industry Rumah Tempe Asli HB Pematangsiantar. In other words, the inventory control carried out by the company is still not yet optimal. By using the EOlQ met mode in managing mobile inventory, Rumah Tempe Asli HB can optimize the cost of mobile inventory.